Recent advances in nanomaterials for the treatment of spinal cord injury. (February 2023) - Gong, Weiquan; Zhang, Tianhui; Che, Mingxue; Wang, Yongjie; He, Chuanyu; Liu, Lidi; Lv, Zhenshan; Xiao, Chunsheng; Wang, Hao; Zhang, Shaokun
Abstract: Spinal cord injuries (SCIs) are devastating. In SCIs, a powerful traumatic force impacting the spinal cord results in the permanent loss of nerve function below the injury level, leaving the patient paralyzed and wheelchair-bound for the remainder of his/her life. Unfortunately, clinical treatment that depends on surgical decompression appears to be unable to handle damaged nerves, and high-dose methylprednisolone-based therapy is also associated with problems, such as infection, gastrointestinal bleeding, femoral head necrosis, obesity, and hyperglycemia. Nanomaterials have opened new avenues for SCI treatment. Among them, performance-based nanomaterials derived from a variety of materials facilitate improvements in the microenvironment of traumatic injury and, in some cases, promote neuron regeneration. Nanoparticulate drug delivery systems enable the optimization of drug effects and drug bioavailability, thus contributing to the development of novel treatments. The improved efficiency and accuracy of gene delivery will also benefit the exploration of SCI mechanisms and the understanding of key genes and signaling pathways. Herein, we reviewed different types of nanomaterials applied to the treatment of SCI and summarized their functions and advantages to provide new perspectives for future clinical therapies. Graphical abstract: Image 1